Role of Lipids in Morphogenesis of T-Cell Microvilli - Cebecauer, Marek (Frontiers in Immunology, 2021)
T cells communicate with the environment via surface receptors. Cooperation of surface receptors regulates T-cell responses to diverse stimuli. Recently, finger-like membrane protrusions, microvilli, have been demonstrated to play a role in the organisation of receptors and, hence, T-cell activation. However, little is known about the morphogenesis of dynamic microvilli, especially in the cells of immune system. In this review, I focus on the potential role of lipids and lipid domains in morphogenesis of microvilli. Discussed is the option that clustering of sphingolipids with phosphoinositides at the plasma membrane results in dimpling (curved) domains. Such domains can attract phosphoinositide-binding proteins and stimulate actin cytoskeleton reorganisation. This process triggers cortical actin opening and bundling of actin fibres to support the growing of microvilli. Critical regulators of microvilli morphogenesis in T cells are unknown. At the end, I suggest several candidates with a potential to organise proteins and lipids in these structures.